Internal Combustion Engines Improving Performance, Fuel Economy and Emissions - Millo, Federico; Postrioti, Lucio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue, consisting of 14 papers, presents the latest findings concerning both numerical and experimental investigations. Their aim is to achieve a reduction in pollutant emissions, as well as an improvement in fuel economy and performance, for internal combustion engines. This will provide readers with a comprehensive, unbiased, and scientifically sound overview of the most recent research and technological developments in this field. More specific topics include: 3D CFD detailed analysis of the fuel injection, combustion and exhaust aftertreatments processes, 1D and 0D, semi-empirical, neural network-based control-oriented models, experimental analysis and the optimization of both conventional and innovative combustion processes.